Investigation of short tandem repeats in major depression using whole-genome sequencing data - Yu, Chenglong; Baune, Bernhard T.; Wong, Ma-Li; Licinio, Julio (Journal of affective disorders, 2018)
Major depressive disorder (MDD) is a leading contributor to global disease burden. Recent studies have shown that genetic factors play significant roles in the susceptibility to this condition; however, the underlying genetic basis currently remains largely unknown. Short tandem repeat (STR) has been proposed as an explanatory factor in the “missing heritability” of complex diseases or traits. We investigated STR variations from 15 MDD patients and 10 ethnically matched healthy controls based on their deep whole-genome sequencing (WGS) data. The lobSTR software was used to computationally determine STRs. The results of the Mexican-American sample showed that STRs are significantly richer in healthy controls than in MDD cases on each of the 23 chromosomes (all false discovery rates, FDR P-values < 0.0062); while for the Australian of European-ancestry sample, there was no statistically significant STRs difference between MDD cases and controls. High quality WGS costs limited obtaining larger datasets. This preliminary work is the first study that STR variations are applied to investigate MDD based on WGS data. The results on Mexican-American population may imply that within the same ancestry, targeted sequencing on a specific chromosome or region of genome would be sufficient for examining the relationship between STR and MDD. Further studies should examine larger sequencing datasets on other ethnic groups. •It is the first study that STRs detected by WGS data were used to investigate MDD.•WGS can detect all private genetic variations including STR within an individual.•We analysed WGS data of 25 human subjects including 15 MDDs and 10 controls.•There were significantly different STR numbers between MDD cases and controls.•The significant difference was found on each chromosome for MA population.